Quantifying forest elephant social structure in Central African bai environments - Vicki Fishlock; Phyllis Lee; Thomas Breuer (Pachyderm)
Relatively little is known of social dynamics in forest elephants (Loxodonta africana cyclotis), although the fission-fusion model of sociality known in savanna elephants (Loxodonta africana africana) is used as a template. Until fission-fusion sociality or an alternative model is demonstrated, our understanding of how elephants use their environment remains incomplete. To date, there have been no published studies of associations between individuals in forest elephants. Direct observations of forest elephants made at forest clearings (bais) are used here as an approach to studying these questions. Bais represent a special environment, providing mineral and food resources, as well as potential social opportunities. We show that forest elephants at Mbeli Bai in Nouabalé-Ndoki National Park have association patterns that are consistent over time, and that certain conspecifics are preferred as associates in the bai environment. Coupled with significant differences in the group size and composition across age-sex classes, and a high proportion of sightings of lone individuals, we argue that the fission-fusion model of elephant sociality appears to hold for the bai environment. The extent of this system and the importance of bais as social resources remain to be explored.